Islands in the energy stream: regional cooperation in the Indian Ocean tourism sector - Roy Smith; Rachel Welton (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This article considers the need to move away from a dependency on fossil fuels towards more sustainable renewable sources of energy production. The focus is on the tourism sector in two Indian Ocean destinations, Mauritius and the Seychelles. The broader aim, however, is to highlight the interconnectedness between public and private stakeholders and how lessons learned from these case studies could have broader applicability elsewhere. ~ Design/research methods: A case study approach has been taken drawing on data supplied by both the private tourism sector in the destinations under consideration and relevant government and regional reports. ~ Conclusions/findings: Progress has been made in the shift towards decarbonisation policies and practices in these destinations. This has been achieved via a cooperative approach between public and private stakeholders, extending the development of renewable energy infrastructure and supply to include sustainable education policies supported by both governments' education departments and vocational programmes implemented by the larger hotels in these destinations. ~ Originality/value of the article: Although there have been other studies conducted on the promotion of renewable energy in small island states, there is a paucity of such research looking specifically at the tourism sector and the role of public/private partnerships in developing broader education for sustainable development programmes. ~ Implications: The case studies focus on highlighting how governments and tourism businesses can work towards shared goals, in this case decarbonisation and education for sustainability. The implication is that such a model could be applied elsewhere with equally positive results.
Keywords: 330